Investigating the dose-response relation between air pollution and total mortality in the APHEA-2 multicity project. Issue 12 (21st November 2003) - Samoli, E; Touloumi, G; Zanobetti, A; Le Tertre, A; Schindler, Chr; Atkinson, R; Vonk, J; Rossi, G; Saez, M; Rabczenko, D; Schwartz, J; Katsouyanni, K
Abstract : Background: Several recent studies have reported significant health effects of air pollution even at low levels of air pollutants, but in most of these studies linear non-threshold relations were assumed. Aims: To investigate the NO2 mortality dose-response association in nine cities participating in the APHEA-2 project using two different methods: the meta-smooth and the cubic spline method. Methods: The meta-smooth method developed by Schwartz and Zanobetti is based on combining individual city non-parametric smooth curves; the cubic spline method developed within the APHEA-2 project combines individual city estimates of cubic spline shaped dose-response relations. The meta-smooth method is easier and faster to implement, but the cubic spline method is more flexible for further investigation of possible heterogeneity in the dose-response curves among cities. Results: In the range of the pollutant common to all cities the two methods gave similar and comparable curves. Using the cubic spline method it was found that smoking prevalence acts as an effect modifier with larger NO2 effects on mortality at lower smoking prevalence. Conclusions: The NO2 –mortality association in the cities included in the present analysis, could be adequately estimated using the linear model. However, investigation of the city specific dose-response curves should precede the application of linear models.